Determinants influencing fishermen’s willingness-to-participate and willingness-to-pay for conservation of small indigenous fishes: a model-based insight from Indian Sundarbans - Roy, Aparna; Naskar, Malay; Sinha, Archana; Manna, Ranjan K.; Sahu, Sanjeev K.; Ekka, Anjana; Das, Basanta K. (Frontiers in Sustainable Food Systems, 2023)
Small indigenous fishes (SIF) not only support livelihood but also provide nutritional security to the rural population of Southern Asia. The overexploitation and profitable extensive aquaculture become threats to their abundance and diversity, especially noticing a sharp decline in the population and diversity in India. Their conservation strategies received little or no attention from researchers. Understanding stakeholders' decision processes are essential in designing effective conservation strategies. This article aims to quantitatively identify factors influencing fishermen's intention to participate and pay for SIF's conservation. We used questionnaire-based survey data, eliciting a response from 100 households involved in local fisheries of rural Indian Sundarbans. A bivariate logistic Generalized Additive Model is employed, which provides critical insight into fishermen's decision processes on the willingness-to-participate and willingness-to-pay in SIF's conservation programme. The results suggest Literacy, Conservation awareness and Occupation are significant factors influencing willingness-to-participate, while Conservation awareness and Household income are the significant determinants of willingnessto-pay. The nonlinear response-age curve for willingness-to-participate, willingness-to-pay, and their interaction has been unravelled. The 45-50 years old age group was identified as the most likely implementers of small indigenous fish conservation strategies. Study revealed that Several strategies recommendations like increase/ extension of conservation awareness programmes, identification of suitable age-group people (with appropriate education, household income and occupation) related to policies were suggestedare pre-forrequisite for formulating SIF's conservation guidelines strategies for the region.